ANALISIS PENGARUH CUSTOMER EXPERIENCE, SERVICE QUALITY, DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN MASKAPAI CITILINK INDONESIA DI BANDAR UDARA INTERNASIONAL JUANDA – SURABAYA - Ibrahim, Isfandi; Febrianto, Gustaf Naufan (Gapenas Publisher, 2025)
The objective of this study is to identify, analyze, and prove the influence of customer experience, service quality, and brand image on customer loyalty of Citilink Indonesia at Juanda International Airport – Surabaya. This research employs a descriptive quantitative approach. The study uses a random purposive sampling technique by collecting data from 112 Citilink customers at Juanda International Airport using a Likert-scale questionnaire, which was then processed using SPSS Version 30. The analytical method applied is multiple linear regression analysis, along with partial and simultaneous tests for hypothesis testing. The classical assumption tests used include the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results of this study indicate that all variables have a positive and significant influence on customer loyalty, with Customer Experience (X1) being the most significant variable among the three, compared to Service Quality and Brand Image.